Kinetic sprint asymmetries on a non-motorised treadmill in Rugby Union athletes - Brown, S. R.; Cross, M. R.; Girard, O.; Brocherie, F.; Samozino, P.; Morin, J.-B. (International Journal of Sports Medicine, 2015)
The purpose of this study was to present a potential link between sprint kinetic (vertical [F V] and horizontal force [F H]) asymmetries and athletic performance during acceleration and maximal velocity (v max) sprinting. Thirty un-injured male rugby athletes performed 8-s sprints on a non-motorised treadmill. Kinetic data were divided into `strong` and `weak` legs based on individually averaged peak values observed during sprinting and were analysed to evaluate asymmetry. Large differences were found between the strong and weak legs in F H during acceleration (4.3 vs. 3.5 N·kg-1) and v max (3.7 vs. 2.8?N·kg-1) sprinting (both ES=1.2), but not in F V (21.8 vs. 20.8 N·kg-1, ES=- 0.6 for acceleration; 23.9 vs. 22.8 N·kg-1, ES=- 0.5 for v max, respectively). Group mean asymmetry was lower in F V compared to F H during acceleration (1.6 vs. 6.8%) and v max (1.6 vs. 8.2%). The range of asymmetry was much lower in F V (0.03-4.3%) compared to F H (0.2-28%). In un-injured rugby athletes, the magnitude and range of asymmetry scores in F H, occurring during acceleration and v max phases, where much greater than those found in F V. These findings highlight the potential for some un-injured athletes to possess kinetic asymmetries known as crucial components for acceleration performance in sprinting.